Diamond as a Platform for Integrated Quantum Photonics (Adv. Quantum Technol. 3/2018). Issue 3 (10th December 2018) - Lenzini, Francesco; Gruhler, Nico; Walter, Nicolai; Pernice, Wolfram H. P.
Abstract : Diamond has emerged as an optimal platform for the realization of fully integrated quantum photonic technologies. In the cover image, a set of electrically tunable color centers supply a source of indistinguishable single photons in different diamond waveguides; a network of directional couplers and opto‐mechanical phase shifters is employed for active manipulation of quantum states of light, which are detected at the output of the circuit by integrated superconducting single photon detectors. For further details see the Review (article number1800061 ) by Wolfram Pernice and co‐workers.